Balloon dilatation of the aortic valve for congenital aortic stenosis in childhood. Issue 2 (February 1989) - Sullivan, I D; Wren, C; Bain, H; Hunter, S; Rees, P G; Taylor, J F; Bull, C; Deanfield, J E
Abstract : Balloon dilatation of the aortic valve was attempted in 34 consecutive children aged 16 months to 17 years (median 7 years), weight range 9-60 (median 22) kg. Previous surgical valvotomy had been performed in two patients (twice in one of them). The valve was not crossed in one patient. In the remaining 33 patients the pressure difference between the left ventricle and the ascending aorta during systole was reduced from 71 (30) to 28 (19) mm Hg. In 24 patients recatheterisation 2-19 (mean 9) months later showed gradients that were similar to those immediately after balloon dilatation (35 (20) v 31 (20) mm Hg). The two patients with the highest residual gradients immediately after balloon dilatation showed a spontaneous reduction in gradient at repeat catheterisation, whereas the patient who had twice had previous surgical valvotomy showed an increase in gradient from 37 to 99 mm Hg over nine months and required aortic root replacement. Balloon dilatation was repeated in two patients and this caused a further reduction in gradient. New aortic regurgitation occurred in nine (27%) patients (grade I, 8; grade II, 1) and aortic regurgitation was exacerbated (grade I to II) in two of the nine with pre-existing aortic regurgitation. External iliac artery avulsion occurred in one (3%) patient and two (6%) required intravenous streptokinase because the femoral artery became occluded. There were no other complications. Open valvotomy was performed in the child in whom the valve was not crossed, but no other child required aortic valve operation. Balloon dilatation of the aortic valve gave reasonable short term palliation and was well tolerated. It is an alternative to surgical valvotomy for initial palliation of congenital aortic stenosis in many children.